Exploration of the underlying mechanisms whereby buyang huanwu decoction improves peripheral neuropathic pain through network pharmacology and molecular docking - CHEN Kaihao; WANG Dongmei (Pifu-xingbing zhenliaoxue zazhi)
[Objective] To explore the mechanisms whereby Buyang Huanwu Decoction (BYHWT) imoroves peripheral neuropathic pain (PNP) through network pharmacology and molecular docking. [Methods] The active ingredients and targets of BYHWT were screened through the ETCM and SwissTargetPrediction databases. Peripheral neuropathic pain-related targets were screened through the GeneCards, OMIM, TTD, and DisGeNET databases. The venn diagram of intersection targets was plotted using the ggvenn package in R. The ″formulated drugs-active ingredients-disease targets″ network was constructed using Cytoscape software. The protein-protein interaction (PPI) network was established using the STRING database. Gene ontology (GO) enrichment analysis and kyoto encyclopedia of genes and genomes (KEGG) pathway enrichment analysis were performed using the clusterProfiler package in R. Molecular docking of core active ingredients and core targets was conducted using the AutoDock software. [Results] A total of 257 active ingredients and 844 affected targets were screened, along with 3 143 peripheral neuropathic pain-related targets and 478 intersection targets. The PPI analysis revealed core targets, including protein kinase Src (SRC), signal transducer and activator of transcription 3 (STAT3), protein kinase B (AKT1), and epidermal growth factor receptor (EGFR). The GO enrichment analysis identified 3 659 GO terms, encompassing 3 206 biological process, 143 cellular component and 310 molecular functions. KEGG enrichment analysis identified 303 signaling pathways, including EGFR tyrosine kinase inhibitor resistance, the AGE-RAGE signaling pathway in diabetic complications, the HIF-1 signaling pathway, and the PI3K-Akt signaling pathway. [Conclusions] Using network pharmacology and molecular docking techniques, the present study reveals that BYHWT ameliorates peripheral neuropathic pain by multiple ingredients, regulating multiple targets and signaling pathways.